LOAN LOSS PROVISIONING BEHAVIOUR: AN ECONOMETRIC ANALYSIS IN INDIAN BANKING - Kalyan Kumar, Divya (2016)
Loan loss provisions is a part of income statement consisting of funds set aside by the bank managers to cover potential loan defaults. This paper examines the loan loss provisioning behaviour by the Indian banking sector during the period 2008-2015. It analysis the Loan Loss Provisioning hypothesis viz. income smoothing, business cycle, capital management and also estimates x-efficiency and check if they influence the loan loss provisioning behaviour. Technical efficiencies are estimated in the first stage of the research using stochastic frontier intermediation approach and deterministic approach. In the second stage, we test the dynamic loan loss provisions model using System Generalised Method of Moments (SGMM) estimator. We find that the average efficiency of the Indian banks from the 2008 global financial crisis to till date is 91.64 percent. In the dynamic LLP model estimation, we find that the X-efficiency does not have a significant effect on the loan loss provisioning behaviour or capital management manipulation by the bank managers, but interestingly we find a pro cyclical effect on the business cycle behaviour and significant negative income smoothing behaviour.